2012
DOI: 10.1007/s10029-012-0925-2
|View full text |Cite
|
Sign up to set email alerts
|

Spigel hernia: a single center experience in a rare hernia entity

Abstract: SH is a rare entity with a wide clinical spectrum and difficulties in preoperative diagnosis. Once the diagnosis of SH is established, a surgical treatment is indicated because of the high complication risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…1 Spigelian hernias usually present at crossing point of semiluminar (spigelian) and arcuate (Douglas) lines. Commonest symptoms are intermittent nonspecific pain and a bulging mass.…”
Section: Discussionmentioning
confidence: 99%
“…1 Spigelian hernias usually present at crossing point of semiluminar (spigelian) and arcuate (Douglas) lines. Commonest symptoms are intermittent nonspecific pain and a bulging mass.…”
Section: Discussionmentioning
confidence: 99%
“…A search using OvidSP and PubMed with the terms 'Spigelian hernia' and 'bilateral' in the title/abstract revealed five articles reporting bilateral cases of Spigelian hernias after excluding those not written in the English language and those reporting congenital paediatric cases. [1][2][3][4][5] Both the laparoscopic and the open approach in their management have been reported. Naik et al describe a case of bilateral hernias in an elderly man that were repaired laparoscopically using two-layered Prolene ® meshes 3 while Safioleas et al describe a more traditional open approach in a middle aged woman.…”
Section: Case Historymentioning
confidence: 99%
“…A paper from 2012 describing 16 cases of Spigelian hernias reported that half of the cases required emergency repair. 2 Management of bilateral hernias is more complex as very few cases are described in the literature. A search using OvidSP and PubMed with the terms 'Spigelian hernia' and 'bilateral' in the title/abstract revealed five articles reporting bilateral cases of Spigelian hernias after excluding those not written in the English language and those reporting congenital paediatric cases.…”
Section: Case Historymentioning
confidence: 99%